Apoptotic-cell-derived membrane microparticles and IFN-α induce an inflammatory immune response - Nießen, Anna; Heyder, Petra; Krienke, Stefan; Blank, Norbert; Tykocinski, Lars-Oliver; Lorenz, Hanns-Martin; Schiller, Martin (Journal of cell science, 2015)
A Section a dysregulation in the clearance of apoptotic material is considered a major pathogenetic factor for the emergence of autoimmune diseases. Apoptotic-cell-derived membrane microparticles (AdMPs), which are released from the cell surface during apoptosis, have been implicated in the pathogenesis of autoimmunity. Also of importance are cytokines, such as interferon-α (IFN-α), which is known to be a major player in patients with systemic lupus erythematosus (SLE). This study investigates the combined effect of AdMPs and IFN-α on professional phagocytes. In the presence of IFN-α, phagocytosis of AdMPs by human monocytes was significantly increased in a dose-dependent manner. The combination of AdMPs and raised IFN-α concentrations resulted in an increase in the secretion of pro-inflammatory cytokines and an upregulation of surface molecule expression involved in antigen uptake. In addition, macrophage polarisation was shifted towards a more inflammatory type of cell. The synergism between IFN-α and AdMPs seemed to be mediated by an upregulation of phosphorylated STAT1. Our results indicate that IFN-α, together with AdMPs, amplify the initiation and maintenance of inflammation. This mechanism might especially play a crucial role in disorders with a defective clearance of apoptotic material.